Pitch Ability As an Aptitude for Tone Learning. Issue 4 (7th January 2016) - Bowles, Anita R.; Chang, Charles B.; Karuzis, Valerie P.
Abstract : Tone languages such as Mandarin use voice pitch to signal lexical contrasts, presenting a challenge for second/foreign language (L2) learners whose native languages do not use pitch in this manner. The present study examined components of an aptitude for mastering L2 lexical tone. Native English speakers with no previous tone language experience completed a Mandarin word learning task, as well as tests of pitch ability, musicality, L2 aptitude, and general cognitive ability. Pitch ability measures improved predictions of learning performance beyond musicality, L2 aptitude, and general cognitive ability and also predicted transfer of learning to new talkers. In sum, although certain nontonal measures help predict successful tone learning, the central components of tonal aptitude are pitch‐specific perceptual measures.